Obesity diagnosis and mortality risk based on a body shape index (ABSI) and other indices and anthropometric parameters in university students - Martina Gažarová; Mária Galšneiderová; Lucia Mečiarová (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Obesity is a global epidemic and belongs to major risk factors for the most prevalent diseases. Anthropometric measures are simple, inexpensive, non-invasive tools to diagnosis obesity and to assess the risk of morbidity and mortality. The most widely used are body mass index (BMI), waist circumference (WC), waist-to-hip (WHR) and waist-to-height ratios, visceral fat area (VFA), body fat (BFP) and a new body shape index (ABSI). Objective. The aim of this study was to examine the usefulness of the ABSI in obesity diagnosis compared with other anthropometric parameters like WC, WHR, BMI, VFA, and BFP. We also compared the predictability between ABSI and above mentioned common anthropometric indices. Material and methods. The study group was composed of 236 university students. Body height, weight, WC was measured and BMI, WHR, ABSI and ABSI z-score were calculated. The anthropometric measurements were made by using InBody 720 (Biospace Co. Ltd., Seoul, Republic of Korea). Body composition, especially VFA, BFP, FFM was diagnosed by multifrequency bioelectrical impedance analysis. We evaluated the collected data statistically and graphically in Microsoft Office Excel 2010 (Los Angeles, CA, USA). Statistical analyses were performed using the program STATISTICA Cz version 10. Results. The diagnosis of obesity among participants according to anthropometric measures and indices showed considerable differences. We found that obesity was diagnosed according to waist circumference in 31% of participants. According to BMI 20.3% of subjects were overweight and 5.1% obese. With increasing BMI values, the values of WC, WHR and VFA also increased linearly. According to visceral fat area 11.4% of participants were in the risk obese group and by ABSI mortality risk there were 22% of subjects with high risk (4.8% and 28.3% for men and women, respectively) and 19.1% with very high risk (11.1% and 22% for men and women, respectively). VFA and BFP values increased with increasing risk of mortality, and in men also waist circumference values. When evaluating the ABSI in relation to BMI, the U-shaped curve was confirmed and in the case of WC the J-shaped curve. The FFM evaluation showed that the very low ABSI mortality risk group reached the highest values of this parameter and the lowest values showed the average mortality risk group, not only in the study group but also in male and female groups. Conclusions. Our findings suggest the relevance of ABSI to screen at-risk population.